Error Analysis of English Written Text of Higher Level English Foreign Language Learners - Idris Rochmadi (International Journal of English Learning and Applied Linguistics (IJELAL), 2020)
The main purpose of this research is to analysis of errors based on surface strategy taxonomy on the students’ English written text. It aims at developing further analyzing of error analysis in second language learners. The approach of research is qualitative descriptive. The samples were taken from the written text made by 20 students in writing development skill class. The findings resulted in: the most common error occurred is omission 45,45%. The second place of frequent is misformation 21,81% as the score. The third is addition 19,09%. The fourth is error on misordering 13,63%. The sources of errors of this research were mother-tongue influence. It was influenced by the native language which interferes with target language learning.